An accurate and efficient framework for modeling multimetal competitive adsorption on clay minerals - Pengyuan Gao; Xiandong Liu; Xiancai Lu; Christophe Tournassat (Proceedings of the National Academy of Sciences, 2026)
Multiple toxic metal elements usually coexist and thus their competitive adsorption always occurs in natural and engineered clay-rich systems. Currently, however, the competitive adsorption mechanisms of multicomponent metal systems on clay mineral surfaces are still unclear, hindering the accurate prediction of toxic metal distribution in soil-water environments. In this study, we uncovered the microscopic mechanism of competitive adsorption of multimetals on heterogeneous clay mineral surfaces using first principles calculation, which indicates that metal ion size largely dominates their complexation on clay mineral surfaces, and competitive adsorption of metals plays a key modulatory role in the adsorption process on clay minerals. By integrating theoretically and experimentally derived multiscale information, a state-of-the-art surface complexation model (SCM) framework has been developed for modeling competitive adsorption. Extensive tests showed that the SCM framework accurately and efficiently reproduces the toxic metal distribution, which enables the quantitative prediction and understanding in realistic environmental conditions. Our results have wide applications in future fundamental studies and the design of environmental materials for toxic metal removal from aquatic systems.